Stereoselective Synthesis and Antiproliferative Activities of Tetrafunctional Diterpene Steviol Derivatives - Bai Dorottya; Schelz Zsuzsanna; Erdős Dóra; Kis Anna K.; Nagy Viktória; Zupkó István; Balogh György Tibor; Szakonyi Zsolt (2023)
A new family of diterpene-type aminotriol derivatives has been synthesised from stevioside in a stereoselective manner. The key intermediate spiro-epoxide was prepared through the methyl ester of the allilyc diol derived from steviol. The oxirane ring was opened with primary and secondary amines, providing a versatile library of aminotriols. The corresponding primary aminotriol was formed by palladium-catalysed hydrogenation, and an N,O-heterocyclic compound was synthesised in a regioselective reaction. All new compounds were characterised by 1D- and 2D-NMR techniques and HRMS measurements. In our in vitro investigations, we found that the aromatic N-substituted derivatives exhibited high inhibition of cell growth on human cancer cell lines (HeLa, SiHa, A2780, MCF-7 and MDA-MB-231). The antiproliferative activities were assayed by the MTT method. Furthermore, the introduction of an additional hydroxy group slightly increased the biological activity. The drug-likeness of the compounds was assessed by in silico and experimental physicochemical characterisations, completed by kinetic aqueous solubility and in vitro intestinal-specific parallel artificial membrane permeability assay (PAMPA-GI) measurements.
Keywords: Általános orvostudomány; Farmakológia és gyógyszerészet